2012
DOI: 10.1093/nar/gks1272
|View full text |Cite
|
Sign up to set email alerts
|

Yeast polypeptide exit tunnel ribosomal proteins L17, L35 and L37 are necessary to recruit late-assembling factors required for 27SB pre-rRNA processing

Abstract: Ribosome synthesis involves the coordinated folding and processing of pre-rRNAs with assembly of ribosomal proteins. In eukaryotes, these events are facilitated by trans-acting factors that propel ribosome maturation from the nucleolus to the cytoplasm. However, there is a gap in understanding how ribosomal proteins configure pre-ribosomes in vivo to enable processing to occur. Here, we have examined the role of adjacent yeast r-proteins L17, L35 and L37 in folding and processing of pre-rRNAs, and binding of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 112 publications
(139 reference statements)
3
59
0
Order By: Relevance
“…More recently, a refined in vivo assembly map was put forward by Chen and Williamson (2013) that largely corresponds to the Nierhaus map (Rohl and Nierhaus 1982). Our collective studies on yeast RPLs (Babiano et al 2012;Jakovljevic et al 2012;Gamalinda et al 2013;Ohmayer et al 2013) show the following differences from bacterial large subunit assembly: First, while incorporation of bacterial RPLs occurs via distinct assembly groups, most yeast RPLs are present in early assembly intermediates but differ in the step of assembly for which they are required and become more stably assembled in a sequential fashion. Second, several assembly relationships observed in bacterial RPLs are not found for their eukaryotic homologs (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…More recently, a refined in vivo assembly map was put forward by Chen and Williamson (2013) that largely corresponds to the Nierhaus map (Rohl and Nierhaus 1982). Our collective studies on yeast RPLs (Babiano et al 2012;Jakovljevic et al 2012;Gamalinda et al 2013;Ohmayer et al 2013) show the following differences from bacterial large subunit assembly: First, while incorporation of bacterial RPLs occurs via distinct assembly groups, most yeast RPLs are present in early assembly intermediates but differ in the step of assembly for which they are required and become more stably assembled in a sequential fashion. Second, several assembly relationships observed in bacterial RPLs are not found for their eukaryotic homologs (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 95%
“…We previously found that abortive assembly intermediates are turned over after depleting RPLs functioning in early and middle steps of pre-60S assembly Gamalinda et al 2013). Preribosomes blocked early in 60S assembly are more rapidly degraded than preribosomes blocked at middle steps, indicating that pre-60S complexes are progressively stabilized through-out successive maturation steps.…”
Section: Preribosomes Become More Stable As Assembly Proceedsmentioning
confidence: 99%
See 3 more Smart Citations